1990
DOI: 10.1021/ac00201a020
|View full text |Cite
|
Sign up to set email alerts
|

The physical sense of simulation models of liquid chromatography: propagation through a grid or solution of the mass balance equation

Abstract: Two distinctly different approaches have been used to simulate the movement of bands through a chromatographic column. One example of the first approach Is the Craig distribution model, which replaces the continuous column with a specific number of discrete equilibration processes. Thus It Introduces the concept of (theoretical) plates Into chromatography, but Is not able to explain satisfactorily their significance. The second approach is based on the mass balance equation which can be Integrated numerically … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
59
0
3

Year Published

1990
1990
2020
2020

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 115 publications
(63 citation statements)
references
References 34 publications
1
59
0
3
Order By: Relevance
“…Here we ¢nd that this is not the case for Btk SH3. Instead, GPC elution pro¢les, intermolecular NMR cross-relaxation and 15 N NMR relaxation measurements are consistent with a monomer^dimer equilibrium with a dissociation constant on the order of 60 WM. In addition, comparison of chemical shifts and resonance linewidths as a function of concentration with those observed in TH-peptide titrations indicate that peptide binding competes with dimerization.…”
Section: Discussionmentioning
confidence: 80%
See 4 more Smart Citations
“…Here we ¢nd that this is not the case for Btk SH3. Instead, GPC elution pro¢les, intermolecular NMR cross-relaxation and 15 N NMR relaxation measurements are consistent with a monomer^dimer equilibrium with a dissociation constant on the order of 60 WM. In addition, comparison of chemical shifts and resonance linewidths as a function of concentration with those observed in TH-peptide titrations indicate that peptide binding competes with dimerization.…”
Section: Discussionmentioning
confidence: 80%
“…For the N-terminally extended SH3 (PRR-SH3), the DNA fragment encoding residues 178^275 of human Btk was ampli¢ed by PCR and the fragment was cloned into the pGEX-4T-3 vector (Amersham Pharmacia Biotech, Sweden) for expression in Escherichia coli BL21 (DE3). The expression and puri¢ca-tion of unlabeled, 15 N-labeled, and 13 C, 15 N-labeled Btk PRR-SH3 and SH3 for the present study was essentially carried out as reported previously [14]. In addition, puri¢ed protein samples were heat-stabilized in Eppendorf tubes at 65³C for 30 min immediately followed by cooling to 4³C and centrifugation at 21 000Ug for 10 min.…”
Section: Cloning Expression and Puri¢cationmentioning
confidence: 99%
See 3 more Smart Citations